Community Participation in the Implementation of Simultaneous Regional Head Elections during the 2020 Covid-19 Pandemic in Banten Province - Dairul; Bahrullah Akbar; Aries Djaenuri; Sampara Lukman (GoAcademica Research & Publishing, 2021)
In terms of community involvement, the conduct of regional head elections embodies the representational function inherent in popular sovereignty. The role of representation is one of the government's functions. As a result, the selection represents the aim of Government Science. The purpose of this research is to assess